High-dispersion organic-inorganic composite flexible thermoelectric material and preparation method thereof
By using conjugated polymers to coat carbon nanotubes in organic-inorganic thermoelectric composite materials and composite them with conductive polymers, the problem of easy agglomeration of carbon nanotubes is solved, significantly improving the dispersion and thermoelectric properties of the materials, and achieving high efficiency energy conversion.
Patent Information
- Application Number
- CN202311030580.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-16
AI Technical Summary
In organic-inorganic thermoelectric composite materials, carbon nanotubes are prone to agglomeration and difficult to disperse well, resulting in insufficient interface contact, increased thermal conductivity but limited room for performance improvement.
After adding carbon nanotubes to the conjugated polymer solution for dispersion, centrifugation and collecting the supernatant, cooling or evaporation and condensation of solids, filtering and washing to remove the outer conjugated polymer, obtaining conjugated polymer thickness coated molecular layer thickness conjugated polymer The highly dispersed carbon nanotubes of the substance are mixed with the conductive polymer to form a film-forming solution for film formation, and finally immersed in the doping solution to obtain a highly dispersed organic-inorganic composite flexible thermoelectric material.
Through supramolecular self-assembly and unbinding carbon nanotubes, their dispersion and electrical transport performance are significantly improved, and the thermoelectric performance is achieved. At the same time, the process conditions are simple, controllable, and production costs are low.
Smart Images

Figure CN119497554A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible thermoelectric material preparation, and in particular relates to a highly dispersed organic-inorganic composite flexible thermoelectric material and a preparation method thereof. Background Art
[0002] Thermoelectric conversion technology is a technology that uses the Seebeck effect and Peltier effect of semiconductor materials to directly convert heat energy and electrical energy. As a new type of clean energy technology, thermoelectric conversion technology has been developed and utilized in the fields of industrial waste heat utilization and solar thermal composite power generation. The thermoelectric performance of thermoelectric materials is generally evaluated by the dimensionless thermoelectric figure of merit ZT, ZT = α 2 σT / κ, where α is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature.
[0003] Flexible thermoelectric materials and devices can obtain heat from the human body or the environment and directly convert it into electrical energy. They are expected to be applied in the fields of the new generation of intelligent micro-nanoelectronic systems represented by distributed, wearable, and implantable devices. Compared with traditional brittle and rigid thermoelectric materials, flexible thermoelectric materials have the following significant advantages: (1) Good flexibility allows them to be in close contact with the heat source surface such as the human body, curved pipes, or flexible electronic devices, thereby minimizing contact heat loss and achieving efficient energy conversion; (2) Light weight, as an independent thin-film thermoelectric material, it can be firmly attached to various flexible substrates such as the human body and clothes, realizing more applications. In recent years, with the development of flexible electronic technology and the growing demand for sustainable and multi-purpose energy harvesting, flexible thermoelectric materials have attracted more and more research interests.
[0004] Traditional inorganic semiconductors and semimetals have extremely high thermoelectric conversion performance, but most of them are brittle and cannot meet the mechanical performance requirements of flexible thermoelectric materials. Organic materials have excellent flexibility and low thermal conductivity, but often have poor electrical transport performance, which is 1-2 orders of magnitude lower than that of classical inorganic materials. Based on the complementary mechanical, thermal and electrical properties of organic and inorganic materials, it is expected that high-performance organic-inorganic thermoelectric composite materials can be developed, which is of great research significance.
[0005] In organic-inorganic thermoelectric composite materials, inorganic materials must be interconnected with organic materials to maintain the integrity and stability of the materials. In addition, carrier conduction channels must be formed to achieve rapid carrier transport and excellent electrical properties. Since the molecular chain of organic materials is a one-dimensional structure, one-dimensional materials (such as nanowires and whiskers) composited with polymers are the preferred materials for designing and preparing organic-inorganic thermoelectric composite materials. Single-walled carbon nanotubes are widely used in the preparation of organic-inorganic thermoelectric composite materials to optimize and regulate their thermoelectric properties due to their unique one-dimensional structure and excellent electron transport properties. However, to obtain high-performance composite materials, a large amount of carbon nanotubes are often required to be added. As the content of carbon nanotubes increases, carbon nanotubes are easy to agglomerate in the polymer matrix and difficult to disperse well, which is not conducive to the effective interface contact between carbon nanotubes and polymers, and leads to an increase in the thermal conductivity of the composite material, so the performance improvement space is limited. How to further improve the dispersibility of carbon nanotubes in the polymer matrix and enhance the interfacial effect is a key issue that needs to be solved to improve the thermoelectric performance of organic / inorganic composite materials.
[0006] In order to effectively deal with the problem of carbon nanotubes being difficult to disperse during the application process, two different methods, covalent and non-covalent functionalization, are generally used to prevent the aggregation of carbon nanotubes, thereby enhancing their dispersibility. However, covalent functionalization is based on the covalent bond of functional groups on carbon carriers. This method destroys the sp2 hybrid network structure of carbon nanotubes and weakens the excellent performance of carbon nanotubes in other aspects. In contrast, the non-covalent bonding method is to adsorb surfactants and polymers on the surface of carbon nanotubes to improve their dispersibility. This modification method can greatly reduce the agglomeration phenomenon caused by electrostatic repulsion and steric hindrance effect without destroying the surface structure of carbon nanotubes. Therefore, in the research of recent decades, people have developed a variety of surfactants to improve the dispersibility of carbon nanotubes, such as sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and hexadecyltrimethylammonium bromide. However, although these dispersants can improve the dispersibility of carbon nanotubes to a certain extent, they are electrically insulating small molecules themselves, which will deteriorate the electrical transport performance of carbon nanotubes. Summary of the invention
[0007] In view of the technical problem that carbon nanotubes are easy to agglomerate in the above-mentioned thermoelectric materials, the present invention aims to provide a method for improving the dispersion of carbon nanotubes and maintaining or improving their electrical transport performance, so as to obtain high-performance organic-inorganic composite flexible thermoelectric materials.
[0008] In a first aspect, the present invention provides a method for preparing a highly dispersed organic-inorganic composite flexible thermoelectric material, comprising: (1) adding carbon nanotubes to a solution of conjugated polymer A to disperse and centrifuge the solution, collecting the supernatant, then cooling or evaporating the supernatant to precipitate a solid, filtering, and washing to remove the outer layer of conjugated polymer A that is not bound to the carbon nanotubes by intermolecular forces, to obtain highly dispersed carbon nanotubes coated with the conjugated polymer A with a molecular layer thickness of 100; (2) The highly dispersed carbon nanotubes coated with the conjugated polymer A with a molecular layer thickness are mixed with a conductive polymer B solution to form a film-forming solution and a film is formed to obtain an organic-inorganic composite flexible thermoelectric film, and then the organic-inorganic composite flexible thermoelectric film is immersed in a doping solution to obtain the highly dispersed organic-inorganic composite flexible thermoelectric material.
[0009] Preferably, the carbon nanotubes are single-walled carbon nanotubes with a diameter of 0.5 to 2 nm and a length of 20 to 30 nm; The conjugated polymer A is an alkyl-substituted conjugated polymer with a molecular weight of 30,000-80,000, preferably polyalkylthiophene or polyalkylselenophene, more preferably one of butyl-substituted polythiophene, hexyl-substituted polythiophene, octyl-substituted polythiophene, octyl-substituted polyselenophene, dodecyl-substituted polythiophene and dodecyl-substituted polyselenophene.
[0010] Preferably, the mass ratio of the conjugated polymer A to the carbon nanotubes is 1:4 to 4:1, preferably 2:1.
[0011] Preferably, the dispersion method is pulse ultrasonic dispersion; wherein the pulse power is 100-1000w, the pulse temperature is 20-80°C, and the pulse time is 10-60min; The centrifugation is performed by high-speed centrifugation; wherein the rotation speed of the high-speed centrifugation is 6000-15000 rpm, and the centrifugation time is 10-60 min.
[0012] Preferably, a solvent at 20-70° C. is used for washing; the mass of the coated molecular layer thickness conjugated polymer A accounts for less than 5% of the mass of the highly dispersed carbon nanotubes coated with the molecular layer thickness conjugated polymer A; and the molecular layer thickness ranges from 0.2 to 2 nm.
[0013] Preferably, the conductive polymer B is at least one of polyaniline, polybenzofuranone, diketopyrrolopyrrole-based conductive polymer and thiophene-based conductive polymer with a molecular weight of 30,000-100,000; preferably, the thiophene-based conductive polymer is poly-3,4-dioxythiophene or poly-3-hexylthiophene.
[0014] Preferably, the mass ratio of the highly dispersed carbon nanotubes of the coated molecular layer thickness conjugated polymer A to the conductive polymer B is 1:4 to 4:1.
[0015] Preferably, the film forming method is drop coating or spin coating, the film forming solvent is toluene, o-xylene, chloroform or tetrahydrofuran, the film forming temperature is 20-60° C., and the film forming time is 0.1-12 h.
[0016] Preferably, the doping solution is an iron salt solution, preferably ferric chloride or bis(trifluoromethanesulfonyl)imide iron solution, the concentration of the iron salt solution is 0.1-1 mol / L, the solvent of the iron salt solution is nitromethane; the immersion time in the doping solution is 0.1-4h; the temperature of the doping solution is 20-40°C.
[0017] In a second aspect, the present invention provides a highly dispersed organic-inorganic composite flexible thermoelectric material obtained according to the above preparation method.
[0018] Beneficial Effects The preparation method provided by the present invention utilizes the intermolecular forces between carbon nanotubes and conjugated polymers to form supramolecular self-assembly between carbon nanotubes and conjugated polymers, thereby achieving debonding between carbon nanotubes, greatly improving the dispersion of carbon nanotubes and maintaining or improving their electrical transport performance; at the same time, the carbon nanotubes coated with conjugated polymers can be composited with a variety of typical conductive polymers, and the highly dispersed composite thermoelectric thin film obtained after film formation has good carbon tube dispersion, and the surface of the film is uniform and continuous, which can achieve significant improvement in thermoelectric performance; The process conditions used in the present invention are simple, highly controllable, highly repeatable, and low in production cost, which greatly increases the practical application space of carbon tube composite polymer thermoelectric materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a transmission electron microscope image of the carbon nanotube coated with the conjugated polymer A with a molecular layer thickness prepared in Example 1 of the present invention; Figure 2 Atomic force microscopy images of the carbon nanotube supramolecular assembly before dispersion (a) and after dispersion (b) in Example 1 of the present invention; Figure 3 Schematic diagram of the thermoelectric properties of the polythiophene / carbon nanotube composite film (a) obtained without supramolecular assembly dispersion and the polythiophene / polymer-coated carbon nanotube composite film (b) obtained after supramolecular assembly dispersion in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.
[0021] The following is an exemplary description of a method for preparing a highly dispersed organic-inorganic composite flexible thermoelectric material provided by the present invention. The preparation method may include the following steps.
[0022] (1) Carbon nanotubes coated with conjugated polymer A. Carbon nanotubes are added to a solution of conjugated polymer A for dispersion, centrifugation and collection of the supernatant, and then the supernatant is cooled or evaporated to concentrate to precipitate solids, filtered, and washed to remove most of the outer layer of conjugated polymer A until the part cannot be washed away due to intermolecular forces, thereby obtaining highly dispersed carbon nanotubes coated with conjugated polymer A with a molecular layer thickness of 1.
[0023] In some embodiments, the carbon nanotube is a single-walled carbon nanotube, which may have a diameter of 0.5 to 2 nm and a length of 20 to 30 nm.
[0024] In some embodiments, the conjugated polymer A can be an alkyl-substituted conjugated polymer with a molecular weight of 30,000-80,000, preferably polyalkylthiophene, polyalkylselenophene, more preferably butyl-substituted polythiophene, hexyl-substituted polythiophene, octyl-substituted polythiophene, octyl-substituted polyselenophene, dodecyl-substituted polythiophene, dodecyl-substituted polyselenophene. When the conjugated polymer A and the carbon nanotubes undergo supramolecular assembly, the side chain of the polymer needs to have a certain length so that the carbon nanotubes can be wrapped to form a certain coating effect and achieve effective dispersion of the carbon nanotubes. Therefore, the conjugated polymer A selected in the present invention has an alkyl side chain. At the same time, in order not to affect the subsequent charge transfer, the skeleton structure of the polymer needs to have a conjugated structure, so the polymer skeleton is selected to be polythiophene and polyselenophene. In addition, if the molecular weight of the conjugated polymer A is too small, the degree of conjugation will be reduced; if the molecular weight is too large, its solubility in the solution will be poor.
[0025] In some embodiments, the mass ratio of the conjugated polymer A to the carbon nanotubes may be 1:4 to 4:1, preferably 2:1. If the amount of the conjugated polymer A is too little, the conjugated polymer will not be able to completely cover the carbon nanotubes, thereby failing to avoid agglomeration between the carbon nanotubes; if the amount of the conjugated polymer A is too much, the conjugated polymers themselves will agglomerate, which is not conducive to the interaction between the conjugated polymer and the carbon nanotubes, and is also not conducive to the dispersion of the carbon nanotubes.
[0026] In some embodiments, the dispersion method can be pulse ultrasonic dispersion, and the pulse ultrasonic dispersion method can promote the formation of supramolecular self-assembly conditions between carbon nanotubes and conjugated polymer A; wherein the pulse power can be 100-1000w (for example, 750w), the pulse temperature can be 20-80℃ (for example, 50℃), and the pulse time can be 10-60min (for example, 30min).
[0027] During the implementation of this scheme, if the power of the pulse ultrasonic dispersion is too small, the agglomerated carbon nanotubes will not be fully separated and will not form sufficient contact with the polymer, so that the carbon nanotubes cannot be completely coated and the dispersion will be poor; if the power of the pulse ultrasonic dispersion is too large, the polymer molecular chain will be broken. If the pulse temperature is too low, the thermal motion of the polymer molecular chain will be restricted, thereby limiting the supramolecular interaction with the carbon nanotubes; if the pulse temperature is too high, the thermal motion of the polymer molecular chain will be intensified, and the molecular chain will be too flexible, making it difficult to form a stable core-shell structure with the carbon nanotubes, and the interaction will be limited. If the pulse time is too short, it is not conducive to the full contact between the polymer and the carbon nanotubes; if the pulse time is too long, the system temperature will rise, and the interaction between the polymer and the carbon nanotubes will be limited.
[0028] In some embodiments, the centrifugation is performed by high-speed centrifugation; wherein the rotation speed of the high-speed centrifugation can be 6000-15000 rpm (eg, 12000 rpm), and the centrifugation time can be 10-60 min (eg, 30 min).
[0029] In some embodiments, a solvent at 20-70°C can be used for washing, while ensuring that the filtrate is clear. The conjugated polymer A / carbon nanotubes are washed with a solvent at a certain temperature until all soluble parts are washed away, leaving only the coating layer that has a strong interaction with the carbon nanotubes. Preferably, the proportion of the coating layer mass to the mass of the highly dispersed carbon nanotubes of the conjugated polymer A in the coating molecular layer thickness can be controlled to be less than 5%.
[0030] In some embodiments, the molecular layer thickness may be in the range of 0.2-2 nm. After washing with a hot solvent, the conjugated polymer A coated on the outer layer of the carbon nanotubes mainly forms a stable structure with the carbon nanotubes through intermolecular forces, and the minimum thickness is the thickness of a single molecular layer coating. Calculated by the polymer bond length, the minimum thickness of a single molecular layer is 0.2 nm. If there are too many layers, the intermolecular forces will be weakened, thereby failing to form a stable coating structure.
[0031] The highly dispersed carbon nanotubes coated with the conjugated polymer A provided by the present invention are uniformly dispersed without agglomeration, so that the carbon nanotubes can be debonded by supramolecular self-assembly. Moreover, the carbon nanotube material coated with the molecular layer thickness conjugated polymer A prepared by the preparation method provided by the present invention has a dispersion of carbon tubes in the carbon nanotube material coated with the molecular layer conjugated polymer A that is significantly better than the dispersion of uncoated carbon nanotubes.
[0032] (2) Conductive polymer composite, film formation and doping. The highly dispersed carbon nanotubes coated with the conjugated polymer A with a molecular layer thickness are mixed with the conductive polymer B solution to form a film-forming solution and a film is formed to obtain an organic-inorganic composite flexible thermoelectric film, and then the organic-inorganic composite flexible thermoelectric film is immersed in a doping solution to obtain the highly dispersed organic-inorganic composite flexible thermoelectric material.
[0033] In some embodiments, the conductive polymer B may be at least one of polyaniline, polybenzofuranone, diketopyrrolopyrrole-based conductive polymer, and thiophene-based conductive polymer with a molecular weight of 30,000-100,000; preferably, the thiophene-based conductive polymer may be poly-3,4-dioxythiophene or poly-3-hexylthiophene.
[0034] In some embodiments, the mass ratio of the highly dispersed carbon nanotubes with a molecular layer thickness of the conjugated polymer A to the conductive polymer B may be 1:4-4:1.
[0035] In some embodiments, the film forming method can be drop coating or spin coating, the film forming solvent can be toluene, o-xylene, chloroform or tetrahydrofuran, the film forming temperature can be 20-60°C, and the film forming time can be 0.1-12h. If the film forming temperature is too low, the solvent will evaporate slowly and the film forming time will be too long; if the film forming temperature is too high, the solvent will evaporate too quickly and a uniform film cannot be formed. At the same time, the film forming method has a greater impact on the film forming time. Generally, the spin coating speed is faster, about 0.1 hours; and the drop coating is determined by the corresponding film forming temperature and solvent volatilization speed, generally between 0.5-12h.
[0036] In some embodiments, the doping solution can be an iron salt solution, preferably ferric chloride, bis(trifluoromethanesulfonyl)imide iron solution, the concentration of the iron salt solution can be 0.1-1 mol / L (e.g. 0.5 mol / L), the solvent of the iron salt solution can be nitromethane; the time of immersion in the doping solution can be 0.1-4h, preferably 0.5-4h (e.g. 2h); the temperature of the doping solution can be 20-40°C. The iron salt solution as a doping solution can ensure a high degree of doping, and the polymer can obtain a high conductivity after doping. At the same time, if the doping time is too short, the doping degree will be low and the polymer conductivity will be too low; if the doping time is too long, the polymer film will fall off and be damaged.
[0037] The preparation method provided by the present invention forms a supramolecular self-assembly between carbon nanotubes and conjugated polymer A by means of the intermolecular force between carbon nanotubes and conjugated polymer A, realizes the debonding between carbon nanotubes, greatly improves the dispersion of carbon nanotubes and maintains or improves their electrical transport performance. At the same time, the carbon nanotubes coated with conjugated polymer A provided by the present invention can be composited with a variety of typical conductive polymers B, and the carbon tubes in the highly dispersed composite thermoelectric film obtained after film formation have good dispersion, and the surface of the film is uniform and continuous, which can achieve a significant improvement in thermoelectric performance. In addition, the process conditions used in the present invention are simple, highly controllable, highly repeatable, and low in production cost, which greatly increases the practical application space of carbon tube composite conjugated polymer thermoelectric materials.
[0038] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0039] Example 1
[0040] (1) Add poly (3-dodecylthiophene) (P3DDT, regularity 98%, molecular weight 50,000) (20 mg) to 50 mL toluene solvent to prepare a toluene solution of poly (3-dodecylthiophene), then add 10 mg single-walled carbon nanotubes (SWNT), and perform pulse ultrasonic dispersion with a pulse power of 750 W, a pulse temperature of 50° C., and a pulse time of 30 min. Then, centrifuge the mixed solution at 12,000 rpm for 30 min to obtain a supernatant, place the mixture in an ice bath overnight (10 hours), and precipitate the polymer-coated carbon nanotubes; filter with suction, and wash with 50° C. toluene until the filtrate is clear. The filtrate obtained is the molecular layer conjugated polymer-coated carbon nanotubes. Wherein, the molecular structure formula of the P3DDT is as follows: (2) The carbon nanotubes coated with molecular layer P3DDT were mixed evenly with poly (3-hexylthiophene) in mass ratios of 1:4, 1:2, 1:1, 2:1 and 4:1 respectively to prepare a film, and placed in a 0.5 mol / L nitromethane solution of iron bis(trifluoromethanesulfonyl)imide for 2 h to obtain a highly dispersed conductive poly (3-hexylthiophene) / P3DDT coated carbon nanotube composite flexible thermoelectric film material.
[0041] Referring to the above preparation process, the uncoated polymer carbon nanotubes were mixed with P3HT (poly 3-hexylthiophene) and P3DDT in the same proportion with the same mass fraction to form a film, and placed in a 0.5 mol / L nitromethane solution of bis(trifluoromethanesulfonyl) iron imide for 2 hours to obtain a conductive poly(3-hexylthiophene) / P3DDT / carbon nanotube composite film material as a comparison.
[0042] The results of the tests showed that the thermoelectric performance of the polymer-coated composite film was significantly improved compared to the carbon nanotube composite film not coated with the polymer.
[0043] Example 2
[0044] (1) Add 20 mg of poly (3-dodecylselenophene) (P3DDSe, regularity 98%, molecular weight 50,000) to 50 mL of toluene solvent to prepare a toluene solution of poly (3-dodecylselenophene), add 10 mg of single-walled carbon nanotubes, and perform pulse ultrasonic dispersion with a pulse power of 750 W, a pulse temperature of 50° C., and a pulse time of 30 min. Then, centrifuge the mixture at 12,000 rpm for 30 min to obtain a supernatant, place the mixture in an ice bath overnight (10 hours), and precipitate the polymer-coated carbon nanotubes. Filter by suction, wash with 50° C. toluene until the filtrate is clear, and the filtrate obtained is the molecular layer conjugated polymer-coated carbon nanotubes. (2) The carbon nanotubes coated with molecular layer P3DDSe were mixed evenly with poly (3-hexylthiophene) in a mass ratio of 1:4, 1:2, 1:1, 2:1 and 4:1 to prepare a film, and placed in a 0.5 mol / L nitromethane solution of iron bis(trifluoromethanesulfonyl)imide for 2 h to obtain a highly dispersed conductive poly (3-hexylthiophene) / P3DDSe coated carbon nanotube composite flexible thermoelectric film material.
[0045] Referring to the above preparation process, the uncoated polymer carbon nanotubes were mixed with P3HT (poly 3-hexylthiophene) and P3DDSe in the same proportion with the same mass fraction to form a film, and placed in a 0.5 mol / L nitromethane solution of bis(trifluoromethanesulfonyl) iron imide for 2 hours to obtain a conductive poly(3-hexylthiophene) / P3DDSe / carbon nanotube composite film as a comparison.
[0046] The results of the tests showed that the thermoelectric performance of the polymer-coated composite film was significantly improved compared to the carbon nanotube composite film not coated with the polymer.
[0047] Figure 1 This is a transmission electron microscope image of the carbon nanotubes coated with the molecular layer thickness conjugated polymer A prepared in Example 1 of the present invention. It can be seen from the figure that the outer layer of each carbon nanotube is coated with the conjugated polymer A, and the diameter after coating is about 3-4 nm.
[0048] Figure 2The atomic force microscope images of the carbon nanotubes before (a) and after (b) the supramolecular assembly dispersion in Example 1 of the present invention are shown. As can be seen from the figure, the carbon nanotubes before the supramolecular assembly dispersion are not coated with the conjugated polymer A, and the carbon nanotubes are severely agglomerated, and the diameter of the carbon nanotube bundle is relatively large, at hundreds of nanometers; while the carbon nanotubes after the supramolecular assembly dispersion and washing have good dispersion due to the presence of the molecular layer coated conjugated polymer A on their outer layer, and the diameter of the carbon nanotube bundle is tens of nanometers.
[0049] Figure 3 The thermoelectric performance diagram of the polythiophene / carbon nanotube composite film (a) obtained without supramolecular assembly dispersion and the polythiophene / polymer-coated carbon nanotube composite film (b) obtained after supramolecular assembly dispersion in Example 1 of the present invention is shown in the figure. It can be seen from the figure that when carbon nanotubes and carbon nanotubes coated with P3DDT of the same mass ratio (50%) are composited with poly 3-hexylthiophene, the thermoelectric performance of the composite film obtained by the carbon nanotubes coated with polymers is significantly better than that of the film obtained by the carbon nanotubes not coated with polymers, which is nearly twice as high; at the same time, as a control, the thermoelectric performance of the single coated polymer P3DDT is very low, so it can be ruled out that it is due to the introduction of P3DDT.
[0050] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a highly dispersed organic-inorganic composite flexible thermoelectric material, characterized in that: include: (1) adding carbon nanotubes to a solution of conjugated polymer A to disperse and centrifuge the solution, collecting the supernatant, then cooling or evaporating the supernatant to precipitate a solid, filtering, and washing to remove the outer layer of conjugated polymer A that is not bound to the carbon nanotubes by intermolecular forces, to obtain highly dispersed carbon nanotubes coated with the conjugated polymer A with a molecular layer thickness of 100; (2) The highly dispersed carbon nanotubes coated with the conjugated polymer A with a molecular layer thickness are mixed with a conductive polymer B solution to form a film-forming solution and a film is formed to obtain an organic-inorganic composite flexible thermoelectric film, and then the organic-inorganic composite flexible thermoelectric film is immersed in a doping solution to obtain the highly dispersed organic-inorganic composite flexible thermoelectric material.
2. The preparation method according to claim 1, characterized in that: The carbon nanotubes are single-walled carbon nanotubes with a diameter of 0.5 to 2 nm and a length of 20 to 30 nm; The conjugated polymer A is an alkyl-substituted conjugated polymer with a molecular weight of 30,000-80,000, preferably polyalkylthiophene or polyalkylselenophene, more preferably one of butyl-substituted polythiophene, hexyl-substituted polythiophene, octyl-substituted polythiophene, octyl-substituted polyselenophene, dodecyl-substituted polythiophene and dodecyl-substituted polyselenophene.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the conjugated polymer A to the carbon nanotubes is 1:4 to 4:1, preferably 2:
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that The dispersion method is pulse ultrasonic dispersion, wherein the pulse power is 100-1000w, the pulse temperature is 20-80°C, and the pulse time is 10-60min; The centrifugation is performed by high-speed centrifugation; wherein the rotation speed of the high-speed centrifugation is 6000-15000 rpm, and the centrifugation time is 10-60 min.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Washing is performed using a solvent at 20-70°C; the mass of the coated molecular layer thickness conjugated polymer A is controlled to account for less than 5% of the mass of the highly dispersed carbon nanotubes coated with the molecular layer thickness conjugated polymer A; the molecular layer thickness ranges from 0.2 to 2 nm.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The conductive polymer B is at least one of polyaniline, polybenzofuranone, diketopyrrolopyrrole-based conductive polymer and thiophene-based conductive polymer with a molecular weight of 30,000-100,000; preferably, the thiophene-based conductive polymer is poly-3,4-dioxythiophene or poly-3-hexylthiophene.
7. The preparation method according to any one of claims 1 to 6, characterized in that The mass ratio of the highly dispersed carbon nanotubes with a coating molecular layer thickness of the conjugated polymer A to the conductive polymer B is 1:4 to 4:
1.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The film forming method is drop coating or spin coating, the film forming solvent is toluene, o-xylene, chloroform or tetrahydrofuran, the film forming temperature is 20-60° C., and the film forming time is 0.1-12 hours.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The doping solution is an iron salt solution, preferably ferric chloride or bis(trifluoromethanesulfonyl)imide iron solution, the concentration of the iron salt solution is 0.1-1 mol / L, and the solvent of the iron salt solution is nitromethane; the immersion time in the doping solution is 0.1-4 hours; and the temperature of the doping solution is 20-40°C.
10. A highly dispersed organic-inorganic composite flexible thermoelectric material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing dispersant-free semi-conductive single-walled carbon nanotube film
CN105585000A
Poly (thienopyrazine) / carbon nanotube composite thermoelectric material and preparation method thereof
CN106876572A
Flexible thermoelectric thin film and preparation and application thereof
CN114975756A
Preparation method of thermoelectric material comprising carbon nanotube and conductive polymer, and the thermoelectric material thereby
KR1020160118408A
Carbon nanotube organic semiconductor, method for producing same, and transistor for chemical sensor using same
WO2015199488A1